Human Development Index and Labor Productivity in Central Sulawesi Province: Granger Causality Test and Panel Data Regression - Suparman Suparman; Wahyuningsih Wahyuningsih (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of the human development index (HDI) on labor productivity. This study used panel data by district/city in Central Sulawesi Province in 2017-2020. The analytical method used is the Granger Causality Test and the panel data regression model. This study found that first labor Productivity (LP) had a positive and significant effect on the productivity index (PI). Second is the open unemployment rate (OUR) has a positive and significant effect on the human development index (HDI). Third, the open unemployment rate (OUR) has a negative and significant effect on the labor force participation rate (LFPR).